Iatrogenic Supravalvular Aortic Stenosis Detected by Transesophageal Echocardiography in a Pediatric Patient Undergoing Cardiac Surgery. (January 2015) - Lee, Ji-Hyun; Nam, Karam; Park, Yong-Hee; Kim, Jin-Tae
<x xml:space="preserve">Abstract</x> Supplemental Digital Content is available in the text.